2008
DOI: 10.4012/dmj.27.133
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fluoride Released from Fluoride-containing Dental Restoratives on NiTi Orthodontic Wires

Abstract: The present study investigated the effect of fluoride released from dental restoratives on orthodontic NiTi wires. Five different restoratives (four fluoride-containing and one non-fluoride-containing) and four different NiTi wires were examined in this study. The pH of artificial saliva (AS) was adjusted to 2.5 and 6. Content of released fluoride was determined daily for 10 days. The morphology of wires was observed using a scanning electron microscope. After immersion for 10 days, the initial microhardness o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 19 publications
0
5
0
2
Order By: Relevance
“…[29][30] These results are in agreement with other studies. [30][31] These studies reported significant differences in surface characteristics between control and other tested groups of the different metal archwires and brackets in different electrolyte solutions.…”
Section: Discussionmentioning
confidence: 98%
“…[29][30] These results are in agreement with other studies. [30][31] These studies reported significant differences in surface characteristics between control and other tested groups of the different metal archwires and brackets in different electrolyte solutions.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, the current study aimed at exploring the effects of APF agent that was applied in vitro and in situ [151617] on a Ni-Ti orthodontic wire and comparing them to the conventionally used stainless steel orthodontic wire. All the tested wires used in this study were rectangular wires because these types of wires offer control in all the three planes which facilitated their testing procedures.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that few ten ppm F ions is not enough to corrode the Ni-Ti and Ni-Ti-Cu wires in acidic artificial saliva for 10-day immersion [31]. In this study, the presence of 0.2% NaF (F ions = 950 ppm) in artificial saliva increased the corrosion rates (about 1.5-4 times) and anodic currents at 0 V (about 7.5-27 times) of the test Ti-containing wires, as compared to those obtained in fluoride-free artificial saliva (Table 3).…”
Section: Cyclic Potentiodynamic Polarization Curvementioning
confidence: 99%